Characterization of a decellularized pericardium extracellular matrix hydrogel for regenerative medicine: insights on animal-to-animal variability - Di Francesco, Dalila; Marcello, Elena; Casarella, Simona; Copes, Francesco; Chevallier, Pascale; Carmagnola, Irene; Mantovani, Diego; Boccafoschi, Francesca (Frontiers in Bioengineering and Biotechnology, 2024)
In the past years, the use of hydrogels derived from decellularized extracellular matrix (dECM) for regenerative medicine purposes has significantly increased. The intrinsic bioactive and immunomodulatory properties indicate these materials as promising candidates for therapeutical applications. However, to date, limitations such as animal-to-animal variability still hinder the clinical translation. Moreover, the choice of tissue source, decellularization and solubilization protocols leads to differences in dECM-derived hydrogels. In this context, detailed characterization of chemical, physical and biological properties of the hydrogels should be performed, with attention to how these properties can be affected by animal-to-animal variability. Herein, we report a detailed characterization of a hydrogel derived from the decellularized extracellular matrix of bovine pericardium (dBP). Protein content, rheological properties, injectability, surface microstructure, in vitro stability and cytocompatibility were evaluated, with particular attention to animal-to-animal variability. The gelation process showed to be thermoresponsive and the obtained dBP hydrogels are injectable, porous, stable up to two weeks in aqueous media, rapidly degrading in enzymatic environment and cytocompatible, able to induce a significant increase ofmaintain cell viability in human mesenchymal stem stromal cells. Results from proteomic analysis proved that dBP hydrogels are highly rich in composition, preserving bioactive proteoglycans and glycoproteins in addition to structural proteins such as collagen. With respect to the chemical composition, animal-to-animal variability was shown, but the biological properties were not affected, which remained consistent in different batches. Taken together these results show that dBP hydrogels are excellent candidates for regenerative medicine applications.